Physical vapor growth of double position boundary free, quasi-bulk 3C-SiC on high quality 3C-SiC on Si CVD templates - Schuh, Philipp; Vecera, Philipp; Hirsch, Andreas; Syväjärvi, Mikael; Litrico, G.; La Via, F.; Mauceri, M.; Wellmann, Peter (Materials Science Forum, 2016)
We have developed and investigated the quasi-bulk crystal growth of 3C-SiC on transferred, high quality, CVD-grown templates using a sublimation sandwich technique. The 3CSiC seeding template layers grown on silicon were removed from the silicon carrier using a solution of hydrofluoric acid, nitric acid and water and glued to a SiC substrate using carbon glue. The transferred layers were used as seeding material to grow high quality, single crystalline, double position boundary free 3C-SiC crystals with thicknesses of up to 860 μm and a size of 18 x 20 mm. Analysis of the bulk-like 3C-SiC layers was carried out using Laue measurement in back-reflecting geometry, Raman spectroscopy and optical microscop
Keywords: 3C-SiC; DPBs free; Quasi-bulk; Seed transfer/stabilization; Seeded sublimation epitaxy